2019
DOI: 10.1021/acs.accounts.9b00115
|View full text |Cite
|
Sign up to set email alerts
|

Seven Clues to Ligand Noninnocence: The Metallocorrole Paradigm

Abstract: CONSPECTUS: Noninnocent ligands do not allow an unambiguous definition of the oxidation state of a coordinated atom. When coordinated, the ligands also cannot be adequately represented by a classic Lewis structure. A noninnocent system thus harbors oxidizing (holes) or reducing equivalents (electrons) that are delocalized over both the ligand and the coordinated atom. To a certain degree, that is true of all complexes, but the phenomenon is arguably most conspicuous in complexes involving ligands with extended… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
97
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(114 citation statements)
references
References 66 publications
12
97
0
Order By: Relevance
“…The blue-shi and increased intensity of the Cr K-pre-edge of 3 are consistent with the previous polarized Cr K-edge XAS study on high-valent Cr IV [TTP]O and Cr V [TTP]N, which showed a nearly 1 eV shi on going from the Cr(IV) to the Cr(V) complex. 8 The study also showed that the pre-edge feature observed at $5990 eV is almost completely z-polarized, consistent with the fact that the pre-edge transitions are extremely weak, electric quadrupole-allowed transitions that gain intensity through 3d z 2 -4p z mixing. Accordingly, the Cr center in 3 may be assigned as Cr(V).…”
Section: Resultssupporting
confidence: 59%
See 1 more Smart Citation
“…The blue-shi and increased intensity of the Cr K-pre-edge of 3 are consistent with the previous polarized Cr K-edge XAS study on high-valent Cr IV [TTP]O and Cr V [TTP]N, which showed a nearly 1 eV shi on going from the Cr(IV) to the Cr(V) complex. 8 The study also showed that the pre-edge feature observed at $5990 eV is almost completely z-polarized, consistent with the fact that the pre-edge transitions are extremely weak, electric quadrupole-allowed transitions that gain intensity through 3d z 2 -4p z mixing. Accordingly, the Cr center in 3 may be assigned as Cr(V).…”
Section: Resultssupporting
confidence: 59%
“…The sterically hindered TMP ligands was chosen to improve the stability of the Cr(IV) complex, but the differences in peripheral transition metal d electron counts, XAS has only been infrequently applied to Cr porphyrins and indeed to metalloporphyrin-type complexes in general, except for those involving Mn and Fe. [1][2][3][4][5][6][7][8] Indeed, only one directly relevant study has been reported in the literature, focusing on Cr IV [TTP]O and Cr V [TTP]N, where TTP 2À is the dianion of meso-tetra(p-tolyl) porphyrin. 9 Understandably, we have used substantially improved theoretical methods in the present study to model the Cr K-edge XAS data on the high-valent compounds 2 and 3, and where appropriate, we will point out similarities and differences relative to the earlier study.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] Of particular interest are chelating ligands that both impose steric constraints and enhance the chemical robustness of the transition metal complex, whilst simultaneously having energetically accessible orbitals for reduction or oxidation. [6][7][8][9] A variety of bidentate ligands have been shown to exhibit benecial redox-activity and cooperative metal-ligand reactivites. Overwhelmingly, this behavior is monopolized by ligands that form ve-membered chelate rings.…”
Section: Introductionmentioning
confidence: 99%
“…90 ionization, respectively (assuming that no electronic rearrangement occurs after ionization). Thus, as the electron is ejected from the ligand (which is, in this case, termed as "non-innocent" ligand), [93][94] one can assume that the less interaction the ligand has with the metal, then the more density remains on it which accordingly increases its stability and therefore its ionization energy.…”
Section: Resultsmentioning
confidence: 99%